Proceedings of the Sixteenth ACM Conference on Economics and Computation 2015
DOI: 10.1145/2764468.2764501
|View full text |Cite
|
Sign up to set email alerts
|

Designing Matching Mechanisms under General Distributional Constraints

Abstract: In this paper, we consider two-sided, many-to-one matching problems where agents in one side of the market (schools) impose some distributional constraints (e.g., a maximum quota for a set of schools), and develop a strategyproof mechanism that can handle a very general class of distributional constraints. We assume distributional constraints are imposed on a vector, where each element is the number of contracts accepted for each school. The only requirement we impose on distributional constraints is that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…Controlled school choice is a recent attempt at incorporating political aims, e.g. desegregation (Cantillon, 2017) by using quotas (Kamada and Kojima, 2015;Goto et al, 2017). Such policies therefore represent an alternative to changing attendance boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled school choice is a recent attempt at incorporating political aims, e.g. desegregation (Cantillon, 2017) by using quotas (Kamada and Kojima, 2015;Goto et al, 2017). Such policies therefore represent an alternative to changing attendance boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…7 Another possible direction of research is to study more general feasibility constraints. Kamada and Kojima (2016b) allow for a broader class of upper-bound constraints than those presented here (Goto et al (2016b) also study that class of constraints). This class of constraints, however, excludes lowerbound (floor) constraints, which are studied by Ehlers et al (2014), Goto et al (2016a), and Fragiadakis and Troyan (2016), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Goto et al (2016b) propose a mechanism that is strategy-proof for doctors in the same environment as Kamada and, but the outcome of their mechanism is not weakly stable.8 Kojima, Tamura and Yokoo (2015) explore this connection through the theory of discrete convex analysis.…”
mentioning
confidence: 99%
“…Even though this is a strong assumption, it is a necessary condition for the existence of a feasible matching in our model. The same assumption is widely used in existing works [2,15,18,43]. Moreover, to guarantee the existence of a feasible matching, ratio must be at…”
Section: Modelmentioning
confidence: 97%
“…Developing a non-trivial strategyproof and fair mechanism that can handle ratio constraints is theoretically interesting and challenging. In existing works, it is shown that if constraints belong to a well-behaved class (which is called M-convex set), then a mechanism called generalized DA, which is based on DA, is strategyproof and fair [18,30]. As we discuss later, ratio constraints do not belong to this class.…”
Section: Introductionmentioning
confidence: 99%